Prediction of interfacial behaviour of single flax fibre bonded to various matrices by simulation of microdroplet test - Shaima Bellil; Delphin Pantaloni; Darshil U. Shah; Antoine Le Duigou; Christophe Baley; Johnny Beaugrand; Alain Bourmaud; Sofiane Guessasma (Composites Part C: Open Access, 2023)
The microdroplet test is commonly used to determine the apparent interfacial shear strength (IFSS) of fibre-reinforced microcomposites. A deeper analysis of the test outcome can provide meaningful information about the fibre/matrix interface behaviour if a predictive approach is adopted. In this study, this predictive approach was used to investigate the quality of interface for polymer drops bonded single flax fibre at the microscale. Microdroplets of five thermoplastics matrices were prepared with single flax fibres. Microbond test was performed to assess the force–displacement curves of the studied composite systems. In addition, a finite element (FE) modelling methodology was adopted to quantify the interfacial role by proposing an interfacial constitutive law including the debonding stage. The numerical sensitivity results reveal the leading role of the interfacial stiffness as well as the fibre–matrix separation displacement in triggering the debonding behaviour. In addition, the numerical responses show strong matching with experimental trends using the proposed interfacial model for a wide variety of fibre/matrix interactions. The identification of the mechanical behaviour of the considered composite system shows that the best performing system is flax fibre/PLA, allowing a maximum fibre–matrix separation of 156 µm and an interfacial stiffness of 47 GPa/mm. The worst performing system is flax fibre/PP, which has a limited fibre–matrix separation of 55 µm. This study concludes that the proposed numerical model is able to capture the interfacial shear behaviour of polymeric drops bonded to a single flax fibre, which allows its extension at the mesoscale for a given arrangement of flax fibres in the bio-based composites.